Teachers' Teaching Style as Perceived by Students and its Influence on Students' Level of Self-Regulation and Motivation in Learning Psychology - Avecilla, Paul Adrian; Capiña, Xyron Earl R.; Javier, Aliah Yvonne (Technium Social Sciences Journal, 2023)
The emergence of COVID-19 resulted from educational institutions to adapt flexible mode of learning. In this type of modality, teacher’s teaching styles is one of the crucial factors that may influence the student’s motivation in learning. This quantitative descriptive-correlation study investigated both the students’ perception on what type of teaching style their teachers have and students’ level of motivation in learning Psychology subjects. Data was collected from 349 students taking BS Psychology from Dalubhasaan ng Lungsod ng San Pablo, a locally funded college in the City of San Pablo, Philippines. Results shows that as perceived by the students, 86% of their teachers used learner-centered approach while the remaining 14% used teacher-centered approach. Participation in the learning process is the most common approach used by teachers for specific teaching styles, followed by personalizing experience, relating to experience, and climate building, in that order. Students' motivation to learn psychology was found to be high to very high, as was their self-regulation level. Learner-centered, participation in the learning process, personalizing experience, relating to experience, and climate building was found to have low positive correlation to intrinsic motivation and task value but have negligible correlation to extrinsic motivation and self-regulation.